PENERAPAN MEDIA ULAR TANGGA WAYANG SUKURAGA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SEKOLAH DASAR - Anjali, Salma Isni; Maula, Luthfi Hamdani; Nurmeta, Irna Khaleda; Lyesmaya, Dyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The problem in this study is the lack of use of learning media to support learning, especially social studies subjects with the stigma of social studies subjects simply memorizing it so that what happens is only getting bored learn. This research is a PTK with 4 meetings, where the purpose of this research is to find out the activities of educators, students' critical thinking skills, and learning outcomes through the medium of wayang sukuraga snakes and ladders. The results of this study indicate that before the action was taken, only 60% of students completed their learning outcomes with an average score of 60. After the action was taken in cycle I there was an increase in student learning outcomes to 69% with an average score of 69 and in cycle II there was again increasing the proportion of student learning outcomes to 79& with an average value of 80. So it can be concluded that the application of the Wayang Sukuraga snake and ladder media can help students achieve optimal learning outcomes in social studies subjects and interesting wayang Sukuraga illustrations. Keywords: Learning Outcomes IPS, Snakes and Ladders, Wayang Sukuraga